PELATIHAN PENYUSUNAN LKS BERBASIS KURIKULUM 2013 PADA MATA PELAJARAN EKONOMI DAN AKUNTANSI DI SMA/SMK SWASTA SE-KECAMATAN KEMUNING PALEMBANG - Fitriyanti Fitriyanti; Dwi Hasmidyani; Ikbal Barlian; Firmansyah Firmansyah; Karolus S Waikelak (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2014)
The transition of KTSP curriculum to the 2013 curriculum requires the ability of teachers to create and develop their own LKS. Lack of training on the preparation of LKS based on Curriculum 2013 for private SMA / SMK teachers in Kecamatan Kemuning Palembang encourages the implementation of devotion activities. this. During this time many who get training are teachers from public schools. This activity aims to improve the knowledge, skills and motivation of trainees about the preparation of LKS based on Kurilnilum 2013 on Economic and Accounting Subjects in SMA / SMK in Kemuning Sub-district Palembang. The target of this activity is expected the teachers of SMA and SMK private sector Kemuning Sub-Palembang can arrange LKS based on Curriculum 2013 on Ekonoini and Accounting subjects. While the form of services in the form of training and LKS prepared by participants in groups. Implementation of this activity using the method of assistance. The results of this observation indicate that this is supported by questionnaires and interviews so that it can be concluded that this training has been able to increase knowledge, skill and motivation in the preparation of LKS based on Curriculum 2013. The weakness encountered in this training is the lack of clarity of the issues raised. Therefore it is recommended to weld problems in LKS using operational verbs.